THE EFFECT OF PEDAGOGIC COMPETENCE AND MOTIVATION ON TEACHER PERFORMANCE AT SMK NUR AZIZI TANJUNG MORAWA - Tyssa Thinandra Putri; Ilham Sonata; M. Tahir (CV. RADJA PUBLIKA, 2025)
This study aims to analyze the influence of Pedagogical Competence and Motivation on Teacher Performance at SMK Nur Azizi Tanjung Morawa. Pedagogical Competence is the most important factor in improving the quality of learning so that work motivation can encourage teachers to carry out their duties well. The research method used in this study is a quantitative method with a multiple linear regression approach. Data collected through questionnaires distributed to teachers of SMK Nur Azizi, then analyzed using validity tests, reliability tests, classical assumptions and hypothesis tests. The results of the study indicate that Pedagogical Competence has a positive and significant effect on teacher performance, as well as work motivation which has a positive impact on improving teacher performance. Simultaneously, Pedagogical Competence and work motivation together provide a significant contribution to teacher performance. With the results of the study (1) Pedagogical Competence has a significant effect on teacher performance as seen from the significant value (0.264) <0.05 and t count (2.109) > compared to t table (1.6991). (2) Work motivation has a significant influence on teacher performance. This can be seen from the value (0.000) < 0.05 and t count (2.454) > (1.6991). Based on the results of the study, the variables of Pedagogical Competence and Motivation have a positive and significant influence on Teacher Performance at SMK Nur Azizi Tanjung Morawa. It is recommended to conduct periodic evaluations of teacher performance to provide feedback and encourage continuous improvement for the school. And based on the results of the study, the variable of Pedagogical Competence has a positive and significant influence on Teacher Performance at SMK Nur Azizi Tanjung Morawa. Teachers should improve training and development of pedagogical competence through workshops, seminars, and the development of modern technology and learning methods. And Based on the results of the study, the variable of Motivation has a positive and significant influence on Teacher Performance at SMK Nur Azizi Tanjung Morawa. It is recommended to provide incentives and awards to teachers who have high performance as a form of appreciation and motivation to continue to improve the professionalism of educators.